Impact of psychological capital on organizational citizenship behavior: Moderating role of emotional intelligence - Rabindra Kumar Pradhan; Lalatendu Kesari Jena; Pratishtha Bhattacharya (Cogent Business & Management, 2016)
The role of emotional intelligence (EI) towards nurturing citizenship behavior is still imperfectly certified and is awaited for investigation. At the same time, the growing interest in recent years on psychological capital (self-efficacy, hope, resilience, and optimism) within the managerial literature is sparsely researched in Indian context. Therefore, the purpose of the study is set to investigate (a) the relationship of psychological capital (Psycap) on organizational citizenship behavior (OCB) and (b) whether the construct of EI plays a role in moderating the relationships between Psycap and OCB. The study examined employed professionals identified through convenience sampling (N = 212) in Indian manufacturing and service industries. After establishing the psychometric properties of the scales hypotheses were tested through structural equation modeling. The results show that Psycap is positively related to OCB. The study's major hypothesis that EI moderates the relationship between Psycap and OCB was also supported. Implications of the findings as well as recommendations for future studies are discussed.
Keywords: 650